DEVELOPMENT OF TEACHER’S CONFLICTOLOGICAL COMPETENCE IN THE SYSTEM OF METHODICAL WORK OF GENERAL SECONDARY EDUCATIONAL INSTITUTIONS - Kutsenko, Tetiana (Educological discourse, 2020)
The aim of the article is to improve teachers’ conflictological competence in the system of methodical work of institutions of general secondary education. The tasks of the article are to determine the directions of development of teacher’s conflictological competence and to clarify the criteria and indicators of formation of teacher’s conflictological competence. The directions of development of teacher’s conflictological competence have been presented, taking into account teachers’ readiness for conflictological activity. They have meant independent work for experienced teachers and introduction of special seminar “Fundamentals of Pedagogical Conflictology” for beginner teachers. The special seminar has included the use of educational forms and methods aimed at activation of educational-cognitive actions, development of learning independence and creativity of teachers. It has meant the use of lectures and seminars in the form of a dialogue with audience, business and role-playing games, training and testing methods, analysis of incidents and conflicts, work with own biography etc. The main criteria and indicators of formation of teacher’s conflictological competence have been clarified. They are motivational, cognitive and procedural-activity criteria. The motivational criterion included positive attitude and awareness of expediency of acquiring conflictological competence. The cognitive criterion meant completeness of conflictological knowledge. The procedural-activity criterion included the formation of conflictological skills. The main skills are diagnostic (adequate analysis on conflict situation, clear definition of the initial parameters of conflict, the causes of conflict, its participations and their peculiarities, motives and intentions), communicative (ability to engage in dialogue, focusing on the rules of conflict-free communication, peculiarities and emotional state of an interlocutor), regulatory (ability to use effective methods for solving the conflict), prognostic (substantiated prognosis of conflict developments) and reflexive (analysis and correction of own behaviour).